1991
DOI: 10.1080/17450399109428478
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose fermentation capacity of the hindgut and nitrogen turnover in the hindgut of sows as evaluated by oral and intracecal supply of purified cellulose

Abstract: Adult sows fed a constant amount of a basal diet received purified cellulose either orally at levels of 0 and 475 g/animal.d (Experiment 1) or intracecally at levels of 0, 285, 570 and 855 g/animal.d (Experiment 2). Each experiment consisted of subsequent periods of faeces and urine collection with the animals re-allocated to the treatments each time. With that, a total of 36 observations on each parameter was achieved. The faecal samples were analyzed for the contents of organic matter, cell wall carbohydrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Overall, the differences in digestibility and fermentation activity can be explained by the differences in ingredient composition, especially the type and amount of DF and the level of iCP in the natural matrix of the ingredients. Lower ATTD of DM for the ingredients rich in insoluble fibre such as WB and DDGS is in agreement with several previous studies (Bach Knudsen and Hansen, 1991;Kreuzer et al, 1991;Hansen et al, 2006). This effect is ascribed to the higher insoluble DF content of these diets, which negatively affects the accessibility and action of the endogenous enzymes in the upper gut and microbial fermentation in the lower gut (Bach Knudsen, 2001), resulting in lower degradability.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, the differences in digestibility and fermentation activity can be explained by the differences in ingredient composition, especially the type and amount of DF and the level of iCP in the natural matrix of the ingredients. Lower ATTD of DM for the ingredients rich in insoluble fibre such as WB and DDGS is in agreement with several previous studies (Bach Knudsen and Hansen, 1991;Kreuzer et al, 1991;Hansen et al, 2006). This effect is ascribed to the higher insoluble DF content of these diets, which negatively affects the accessibility and action of the endogenous enzymes in the upper gut and microbial fermentation in the lower gut (Bach Knudsen, 2001), resulting in lower degradability.…”
Section: Discussionsupporting
confidence: 91%
“…This is ascribed to the fact that highly fermentable DF fractions, such as hemicellulose and pectin, stimulate bacterial growth in the hindgut. This in turn increases faecal N excretion in the form of bacterial biomass and thus reduces apparent N digestibility (Kreuzer et al, 1991;Hansen et al, 2006). However, this interaction might not only be due to the effect of soluble NSP on the digestive process, but also due to an increase in endogenous N excretion (de Lange et al, 1989;Huisman et al, 1992;Leterme et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fibre additions decreased digestibility of dry DM and crude CP, which is in accordance to numerous other studies (Kreuzer et al 1991;Zhao et al 1996;Hansen et al 2006;Zhao et al 2007). Indeed, the DM digestibility of the fibre sources used in the present study is known to be comparably low especially in case of the pine pollen due to high content of ADF and ADL Zhao et al 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Corresponding to literature data Lindberg 2004b, 2006), the values of pH in ileal and colonic chyme were not affected by additions of insoluble fibre. This reflects the fact that insoluble fibre is hardly degraded by intestinal microbiota during intestinal passage especially when containing major amounts of lignin (Kreuzer et al 1991;Glitso et al 1998); whereas, reductions in pH are observed only at high intake of bacterially fermentable substrates (e.g. Roth et al 1992).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation